UTAUT2 dan DOI: Analisis Pengguna Aktual Layanan Food Delivery (GoFood) di Kota Surabaya - Anisa Fitri Ramadhani; Nurul Azizah (JUSIFO : Jurnal Sistem Informasi, 2022)
The innovation that is applied is not the main idea of the successful application of technology, but how the community responds to the technological innovation. This study aims to determine how much the model variable The Extended Unified Theory of Accaptance and Use of Technology (UTAUT2) combined with the Diffusion of Innovation (DOI) model has a positive and significant effect on Behavioral to Adopt (BIA), and to find out the structural influence of BIA on the Actual Usage (AU) of GoFood service users in Surabaya. The variables from the UTAUT2 and DOI models become factors that support the behavioral intention of users to adopt and use a system in real terms, in this case the GoFood service with users in Surabaya. The results of this study indicate that the hedonic motivation, habit, and compatibility variables are positive and significant on behavioral intention to adopt. The variables of effort expectancy, price value, and relative advantage were declared positive and not significant on behavioral intention to adopt. The performance expectancy variable is stated to be negative and not significant to the behavioral intention to adopt. In addition, the compatibility variable was stated to be significant and acceptable on performance expectancy and effort expectancy.